Echo intensity is negatively associated with functional capacity in older women - Rech, Anderson (Age (Dordr), 2014)
Muscle quality is an important component of the functional profile of the elderly, and previous studies have shown that both muscle quantity and quality independently contribute to muscle strength of the elderly. This study aimed to verify the association between quadriceps femoris muscle quality, analyzed by specific tension and echo intensity (EI), and rate of torque development (RTD) of the knee extensor muscles with the functional performance in elderly active women. Forty-five healthy, active elderly women (70.28 ± 6.2) volunteered to participate in this study. Quadriceps femoris muscle thickness and EI were determined by ultrasonography. Knee extension isometric peak torque and RTD were obtained from maximal isometric voluntary contraction curves. The 30-s sit-to-stand-up (30SS) test and usual gait speed (UGS) test were applied to evaluate functional performance. Rectus femoris EI presented a significant negative correlation with 30SS (r = −0.505, P < 0.01), UGS (r(s) = −0.347, P < 0.05), and isometric peak torque (r = −0.314, P < 0.05). The quadriceps femoris EI correlated negatively with 30SS (r = −0.493, P < 0.01) and isometric peak torque (r = −0.409, P < 0.01). The EI of the quadriceps femoris and all quadriceps muscle portions significantly correlated with RTD. RTD significantly correlated with physical performance in both functional tests (30SS = r = 0.340, P < 0.05; UGS = r(s) = 0.371, P < 0.05). We concluded that muscle EI may be an important predictor of functional performance and knee extensor power capacity in elderly, active women.